Multichamber PLGA Microparticles with Enhanced Monodispersity and Encapsulation Efficiency Fabricated by a Batch‐Microfluidic Hybrid Approach - Sunghak Choi; Bong Su Kang; Geonjun Choi; Minsu Kang; Haena Park; Nahyun Kim; Pahn–Shick Chang; Moon Kyu Kwak; Hoon Eui Jeong; Ho-Sup Jung (Advanced NanoBiomed Research, 2023)
Microparticles with multiple internal chambers hold great promise as drug delivery systems due to their ability to sustain the release of drugs with short half‐lives. However, conventional batch methods used for their fabrication have limitations in terms of encapsulation efficiency and particle size distributions, while microfluidic methods suffer from low production efficiency. Herein, a batch‐microfluidic hybrid method is presented for fabricating poly(DL‐lactic‐co‐glycolic acid) (PLGA) polymeric microparticles with uniformly distributed, multiple inner microchambers. A scalable batch method is utilized for primary water‐in‐oil (W/O) emulsions, combined with a precise microfluidic approach for generating controlled secondary emulsions. This approach results in highly uniform PLGA microparticles with tunable size and improved encapsulation efficiency. Additionally, the effect of polydopamine‐based surface hydrophilic modification of microfluidic channels on drug encapsulation efficiency is investigated, achieving an efficiency of approximately 85%. The prepared multichamber PLGA microparticles exhibit an extended‐release profile without initial burst release, demonstrating their potential for sustained drug delivery in various biomedical applications.